Preservation and rapid purification of DNA from decomposing human tissue samples. (November 2016) - Sorensen, Amy; Rahman, Elizabeth; Canela, Cassandra; Gangitano, David; Hughes-Stamm, Sheree
Highlights: We evaluated five DNA preservatives (modified TENT, DESS, LST, RNA later and DNAgard ® ) on decomposing tissues stored in hot and humid conditions. A marked decrease in DNA quantity and quality was observed in all samples after the bodies entered the bloat stage of decomposition. Similar amounts of DNA were retrieved from skin and muscle samples over time, but slightly more complete STR profiles were obtained from muscle tissue. Although higher amounts of DNA were recovered from tissue samples, the completeness of STR profiles from "free DNA" in solution was comparable. DNAgard ® and the modified TENT buffer were the most successful preservatives based on STR success from "free DNA" in solution. Abstract: One of the key features to be considered in a mass disaster is victim identification. However, the recovery and identification of human remains are sometimes complicated by harsh environmental conditions, limited facilities, loss of electricity and lack of refrigeration. If human remains cannot be collected, stored, or identified immediately, bodies decompose and DNA degrades making genotyping more difficult and ultimately decreasing DNA profiling success. In order to prevent further DNA damage and degradation after collection, tissue preservatives may be used. The goal of this study was to evaluate three customized (modified TENT, DESS, LST) and two commercial DNA preservatives (RNA later and DNAgard ® ) on fresh and decomposed human skin and muscle samples stored in hot (35 °C) and humid (60–70% relative humidity) conditions for up to three months. Skin and muscle samples were harvested from the thigh of three human cadavers placed outdoors for up to two weeks. In addition, the possibility of purifying DNA directly from the preservative solutions ("free DNA") was investigated in order to eliminate lengthy tissue digestion processes and increase throughput. The efficiency of each preservative was evaluated based on the quantity of DNA recovered from both the "free DNA" in solution and the tissue sample itself in conjunction with the quality and completeness of downstream STR profiles. As expected, DNA quantity and STR success decreased with time of decomposition. However, a marked decrease in DNA quantity and STR quality was observed in all samples after the bodies entered the bloat stage (approximately six days of decomposition in this study). Similar amounts of DNA were retrieved from skin and muscle samples over time, but slightly more complete STR profiles were obtained from muscle tissue. Although higher amounts of DNA were recovered from tissue samples than from the surrounding preservative, the average number of reportable alleles from the "free DNA" was comparable. Overall, DNAgard ® and the modified TENT buffer were the most successful tissue preservatives tested in this study based on STR profile success from "free DNA" in solution when decomposing tissues were stored for up to three months in hot, humid conditions.